An Infant with Congenital Diaphragmatic Eventration with Dextrocardia: A Case Report - Ramana Rajkarnikar; Rabin Thami; Priyanka Dahal; Robal Lacaul; Rashmi Shrestha (Journal of Nepal Medical Association, 2022)
Diaphragmatic eventration is a rare condition, and its association with dextrocardia is even a rarer clinical entity. Patients are usually asymptomatic, but the typical features include rapid breathing and recurrent respiratory infections. Here we present a rare case of a seven months old infant, who presented with cough, noisy breathing and chest retraction. The patient was diagnosed to have dextrocardia with diaphragmatic eventration with pneumonia by chest imaging and was treated in coordination with the medical team for underlying pneumonia. Afterwards, plication of the diaphragm was done through the trans-abdominal approach and the symptoms gradually improved postoperatively. For dextrocardia, since there were no structural abnormalities, the patient was kept in regular follow-up in the pediatric cardiology unit. Though most patients are asymptomatic, diaphragmatic eventration increases the risk of recurrent chest infection and hampers the quality of life of the patient, so timely diagnosis and intervention will greatly improve their quality of life.